2015
DOI: 10.1016/j.cegh.2015.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of exclusive breastfeeding in slums of Dibrugarh Town and factors affecting the breastfeeding practice

Abstract: c l i n i c a l e p i d e m i o l o g y a n d g l o b a l h e a l t h 3 (2 0 1 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
6
1
1
Order By: Relevance
“…Another study conducted by Prakash Chandra Joshi et al in Bangladesh (36%) had results consistent with our study (14) . The studies conducted by Aroona Sabin et al in Pakistan (41.5%) and Indrani Gogoi et al in Dibrugarh Town (41%) had slightly higher rates as compared to the rates in our study (19) . A study conducted by Oluwafolahan O. Sholeye et al in Nigeria (56.1%) also reported higher rate of exclusively breast fed children as compared to the results found in our study (1) .…”
Section: Discussioncontrasting
confidence: 47%
“…Another study conducted by Prakash Chandra Joshi et al in Bangladesh (36%) had results consistent with our study (14) . The studies conducted by Aroona Sabin et al in Pakistan (41.5%) and Indrani Gogoi et al in Dibrugarh Town (41%) had slightly higher rates as compared to the rates in our study (19) . A study conducted by Oluwafolahan O. Sholeye et al in Nigeria (56.1%) also reported higher rate of exclusively breast fed children as compared to the results found in our study (1) .…”
Section: Discussioncontrasting
confidence: 47%
“…In the review, we found that middle or higher socioeconomic status [ 25 , 39 , 40 , 41 ], nuclear family [ 42 , 43 , 44 ], small family size [ 42 , 45 ], male children [ 17 , 46 ], female children [ 47 ], preterm birth [ 43 ], smaller babies at birth [ 44 ], lower birth order [ 30 ], maternal age [ 23 , 48 ] (20–25 years [ 37 , 39 ]), higher maternal education [ 42 , 46 , 49 , 50 , 51 , 52 , 53 ], maternal unemployment [ 38 , 45 ], and multiparity [ 39 ] were associated with EBF. Similarly, low socioeconomic status [ 38 ], low maternal education [ 38 , 43 ], employed mothers [ 44 ], and primiparity [ 51 ] and breastfeeding counselling [ 49 , 54 , 55 ] were also associated with EBF. Additionally, some studies found that young maternal age (15–24 years [ 53 ], <20 years [ 44 ]), low socioeconomic status [ 53 ], and urban residence [ 44 ] were associated with low EBF.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, some studies found that young maternal age (15–24 years [ 53 ], <20 years [ 44 ]), low socioeconomic status [ 53 ], and urban residence [ 44 ] were associated with low EBF. In contrast, breastfeeding counselling [ 54 , 56 , 57 ], registration for ANC [ 39 , 41 ], number of ANC visits (≥3 [ 27 , 48 , 51 ], ≥4 [ 51 ], ≥7 [ 48 ]), hospital birthing [ 30 , 41 ], access to the type of birthing assistance, and vaginal birthing [ 26 , 33 , 44 ] were associated with EBF.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 In a similar study done in slums of Dibrugarh Town, reported the prevalence of EBF was 41%. 12 Another study conducted in urban slums, Karnataka, India, found that the prevalence of EBF was only 22%. 13 The findings were in contrast with our study report.…”
Section: Discussionmentioning
confidence: 99%